Effect of Broken Conjugation on the Stretchability of Semiconducting Polymers. Issue 19 (16th August 2016) - Savagatrup, Suchol; Zhao, Xikang; Chan, Esther; Mei, Jianguo; Lipomi, Darren J.
Abstract : Increasing the flexibility of polymer chains is a common method of increasing the deformability of solid polymeric materials. Here, the effects of "conjugation‐break spacers" (CBSs)—aliphatic units that interrupt the sp 2 ‐hybridized backbone of semiconducting polymers—on the mechanical and photovoltaic properties of a diketopyrrolopyrrole‐based polymer are described. Unexpectedly, the tensile moduli and cracking behavior of a series of polymers with repeat units bearing 0%, 30%, 50%, 70%, and 100% of the CBS are not directly related to the percent incorporation of the flexible unit. Rather, the mechanical properties are a strong function of the order present in the film as determined by grazing‐incidence x‐ray diffraction. The effect of the CBSs on the photovoltaic performance of these materials, on the other hand, is more intuitive: it decreases with increasing fraction of the flexible units. These studies highlight the importance of solid‐state packing structure—as opposed to only the flexibility of the individual molecules—in determining the mechanical properties of a conjugated polymer film for stretchable, ultraflexible, and mechanically robust electronics. Abstract : Conjugation‐break spacers lead to unexpected trends in the mechanical and photovoltaic properties of a series of diketopyrrolopyrrole‐based conjugated polymers. This study highlights the importance of solid‐state packing structure in determining the mechanical properties of a conjugated polymer film for stretchable, ultraflexible, and mechanically robust electronics.